Persepsi Pemandu Terhadap Kenderaan Berat di Lebuhraya. - Norazlina, Aziz @ Khalid (2006)
This project paper is done to investigate the perceptions of motorists towards heavy vehicles in highway. The main objective of this study is to know on how the perceptions can make the drivers involve in accident. Besides, it tries to look the differences of male and female perceptions toward heavy vehicles. The finding of this research has found that mostly the respondents who use the North South highway especially those who are traveling from Butterworth to Alor Star, make negative perceptions. Surprisingly, there are not many differences between male and female in making the perceptions toward heavy vehicle. Besides, age factor shows that the adolescent make less negative toward heavy vehicle compared to another range of age. For the hypothesis testing, "danger" perception shows it is a new indicator that make the driver involve in accident.